Pemanfaatan Teknologi Informasi untuk Pembaruan Peta Sarana Desa di Desa Pemagarsari, Parung, Bogor - Eko Hadi Purwanto; Arief Goeritno (Universitas Mathla'ul Anwar Banten, 2019)
UTILIZATION OF INFORMATION TECHNOLOGY FOR UPDATING THE MAP OF VILLAGE FACILITIES IN DESA PEMAGARSARI, PARUNG, BOGOR. A work program to support the updating of the map of village facilities by a number of students belonging to the Group 13 of KKN-TT from Bogor Ibn Khaldun University in Desa Pemagarsari, Parung, Bogor. The process of updating the map of village facilities is in the form of social interaction between students belonging to the Group 13 of KKN-TT Bogor Ibn Khaldun University in 2017 with the target community represented by the staffs of Desa Pemagarsari. This paper aims to convey information about a number of stages for the process of updating and the physical form of updated for the map of village facilities. This paper aims to convey information about a number of stages for the process of updating and the physical form of updated the map of village facilities. A number of stages for the process of updating the map of village facilities, including the preparation of the work team, submission of renewal permits for the map of village facilities, and comparison of secondary and primary data. The physical form of an updated the map of village facilities is a process of renewing and making hardcopy of the map of village facilities of A1 paper size along with a frame and scheduling and submission of a symbolic the map of village facilities to the Head for Desa Pemagarsari.